2012
DOI: 10.1177/0954405412456660
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on die corner accuracy for wire electrical discharge machining of Monel 400 alloy

Abstract: The experimental research presented in this article explores the wire electrical discharge machining of Monel 400 alloy. An L-18 orthogonal array has been used for experimentation by considering machine controllable factors (i.e. wire tension, pulse-on time, pulse frequency, peak current and servo voltage) and machine uncontrollable factors (namely flushing nozzle height, workpiece thickness and corner angle) as process parameters. Using Taguchi methodology, the influence of the process parameters on the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 15 publications
(36 reference statements)
1
30
0
Order By: Relevance
“…3) at the die is much higher than the corner error at the punch, as illustrated by Sarkar et al [11]. Nevertheless, very limited research [9,10] has been reported on die corner accuracy aspects in WEDM. In this research study, an attempt has been made in the view of enhancing die corner accuracy by adopting trim cutting operation.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…3) at the die is much higher than the corner error at the punch, as illustrated by Sarkar et al [11]. Nevertheless, very limited research [9,10] has been reported on die corner accuracy aspects in WEDM. In this research study, an attempt has been made in the view of enhancing die corner accuracy by adopting trim cutting operation.…”
Section: Introductionmentioning
confidence: 94%
“…The WEDM is one of the best cost-effective methods that eliminate secondary operations [1] in producing high-precision dies and tools. Though many precision dies are manufactured using WEDM, very little attempts have been reported [2][3][4][5][6][7][8][9][10] on corner cutting and corner accuracy aspects in WEDM. Achieving a sharp corner for the customer-specified surface and accuracy features is a matter of grave concern in the WEDM process which can be addressed through an appropriate process design by adopting trim cutting operation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was concluded that average surface was improved in liquid nitrogen cooling of the electrode [8]. Experimental study has been done to investigate the influence of process parameters for MRR, SR, Kerf, over cut and corner accuracy by machining of advanced materials by using Taguchi and ANOVA method [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%